Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.19093/res9477
|View full text |Cite
|
Sign up to set email alerts
|

A criminalidade no Estado de Pernambuco: uma análise espacial dos determinantes das ocorrências de homicídios e roubos

Abstract: Pernambuco tem apresentado uma evolução nos Crimes Violentos Letais Intencionais (CVLI) e Crimes Violentos contra o Patrimônio (CVP), a partir de meados de 2016. Diante disso, este trabalho teve como objetivo identificar os componentes socioeconômicos e geográficos determinantes para o crescimento da criminalidade nos municípios do território estadual. Para isto, foram utilizadas a Análise Exploratório de Dados Espaciais (AEDE) e modelos econométricos com componentes espaciais. Os resultados do Índice de Moran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 14 publications
3
3
0
2
Order By: Relevance
“…It was observed that high population concentration is directly related to the occurrences of homicides in the state of Pernambuco. This conclusion was corroborated with the work from [14], who affirmed that homicides are associated with most populous cities [14]. Furthermore, according to [14], locations with greater economic prosperity, in addition to concentrated a high number of inhabitants, also have an ideal environment for violence growth.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…It was observed that high population concentration is directly related to the occurrences of homicides in the state of Pernambuco. This conclusion was corroborated with the work from [14], who affirmed that homicides are associated with most populous cities [14]. Furthermore, according to [14], locations with greater economic prosperity, in addition to concentrated a high number of inhabitants, also have an ideal environment for violence growth.…”
Section: Discussionsupporting
confidence: 52%
“…This conclusion was corroborated with the work from [14], who affirmed that homicides are associated with most populous cities [14]. Furthermore, according to [14], locations with greater economic prosperity, in addition to concentrated a high number of inhabitants, also have an ideal environment for violence growth. Other aspects that can explain the high homicide rates are for instance, a higher proportion of men aged between 18 and 24 years old in relation to the total population [59], the level of income, drug trafficking [60], school lag, among others.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations